INSTRUMEN TES ISLAM KIMIA (ITIK) UNTUK MENDETEKSI PEMAHAMAN LEVEL MIKROSKOPIS MATERI AIR - Wisudawati, Asih Widi (JCER (Journal of Chemistry Education Research), 2017)
The study aims to develop instrument to measurethe level of understanding of students and microscopic level material phase changes of water. The method used is R&D (Research and Development) Borg and Gall, which have procedure were are following step (1) Need assessment/ Plan (2) Design product/ Organization (3) Created product/ implementation. Implementation with one shot design study with samples used a number of 71 students of 10th grade MA Wahid Hasyim and senior high school MBS Yogyakarta. Indicators in the study is the movement and vibration of water particles, the distance between water particles, particle kinetic energy of water, relative atomic mass of water and hydrogen bonding. The results showed an understanding of chemica lmaterial microscopic level is low and spitual attitude as a nurturant effect is high categories.Â